Szumen a pierwsza polska książka o Bułgarii - Jan Herold; Krasimira Kolewa; Desisława Dewora Atanasowa (Postscriptum Polonistyczne)
The topic of this article is the first Polish novel about Bulgaria: Zarnica. It was written by a revolutionary emigrant Zygmunt Miłkowski alias Teodor Tomasz Jeż, who resided in Shumen with over 1000 Polish and Hungarian rebels headed by L. Kossuth and Gen. J. Bem. The contribution of immigrants to the Bulgarian national revival is significant.